The Role of Compensation in Improving the Performance of Lecturers and Employees of the University of Madura Pamekasan - Rika Syahadatina; Junaidi Efendi; Rani Nur Fitriani (Enrichment : Journal of Management, 2022)
Human resource development program is a force that is expected to create new nuances in an effort to improve work performance, one of which is the provision of compensation, where this can motivate employees to improve their performance. This study aims to determine the effect of compensation on the performance of lecturers and employees at the Madura University. Compensation itself is generally divided into direct and indirect compensation. But it can be expanded further into salaries, benefits, incentives and facilities. These variables that want to reveal their influence on the performance of lecturers and employees of the Madura University. The method in this study is a quantitative method using multiple linear regression. The results of the study found that incentives and facilities had a significant effect on the performance of Madura University lecturers and employees. Meanwhile, salary and benefits have no significant effect.